Fractal Symmetry of Protein Exterior - Banerji, Anirban; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2013)
The essential question that fractal dimensions attempt to answer is about the scales in Nature. For a system as non-idealistic and complex as a protein, studying scale-invariance becomes particularly important. Fractal Symmetry of Protein Exterior investigates the diverse facets of the various scales at which we describe protein biophysical and biochemical phenomena. Although these ideas are entirely mathematical, mathematical expositions have been avoided, unless the use of some expressions becomes absolutely obligatory. A first chapter introduce into fractal dimensions, protein exteriors and to methods to study the roughness of surfaces. The main topics covered in the following chapters include: protein-protein interaction interfaces; protein surface-roughness and local shape as well as adhesion on protein and other rough biomolecular surfaces.
Studying protein exterior with fractal dimension -- Characterization of protein-protein interfaces, considering surface-roughness and local shape -- Adhesion on protein (and other rough biomolecular) surfaces.
Keywords: Life sciences; Chemistry -- Mathematics; Biochemistry; Bioinformatics; Life Sciences; Protein Structure; Bioinformatics; Math. Applications in Chemistry; Protein Science